2022
DOI: 10.1111/prd.12450
|View full text |Cite
|
Sign up to set email alerts
|

Illegal drugs and periodontal conditions

Abstract: In recent years, the practice of dentistry and periodontology has become complicated by several risk factors, including the treatment of an increasing number of patients with substance use disorder. This review presents an update in the current literature of the impact of illegal drug use on periodontal conditions and their possible effect as risk factors or indicators. The main illegal drugs that may have an impact on periodontal health and conditions are described, including their effect, medical manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 140 publications
(409 reference statements)
0
4
0
Order By: Relevance
“…CBD can be considered a therapeutic agent for periodontal disease. However, studies have shown the negative effects of cannabis smoking on periodontal health, possibly leading to periodontitis and gingival enlargements 24 . It has been suggested that CBD may promote fibrotic gingival enlargement by increasing the production of fibronectin in gingival fibroblasts 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD can be considered a therapeutic agent for periodontal disease. However, studies have shown the negative effects of cannabis smoking on periodontal health, possibly leading to periodontitis and gingival enlargements 24 . It has been suggested that CBD may promote fibrotic gingival enlargement by increasing the production of fibronectin in gingival fibroblasts 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown the negative effects of cannabis smoking on periodontal health, possibly leading to periodontitis and gingival enlargements. 24 It has been suggested that CBD may promote fibrotic gingival enlargement by increasing the production of fibronectin in gingival fibroblasts. 25 Therefore, the use of CBD in the treatment of periodontitis needs much research.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the practice of dentistry and periodontology has become complicated by the treatment of an increasing number of patients with substance use disorder. 6 There are many illegal drugs that may have an impact on periodontal health and conditions, including their effect, medical manifestations, risks, and overall impact on oral health and the periodontium. The clinical management of periodontal patients abusing illegal drugs has been reported in a comprehensive approach inclusive of the detection of illicit drug abusers, screening, interviewing and counseling, the referral to treatment, and the dental and periodontal management.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to detect a wide range of illicit drugs, such as heroin, cocaine, methamphetamine and mephedrone, is, therefore, a significant challenge whose overcoming will bring great benefits to society. 4,5 The successful detection of such drugs has become a crucial priority to reduce threats and risks to public health, [6][7][8][9][10] which cause serious damage, such as respiratory, cardiac, renal damage and also mental health problems such as violence, depression, anxiety and hallucinations. 11,12 In order to design sensitive, fast, portable, and low-cost sensing nanodevices, it is necessary to develop new nanomaterials and device concepts, and devise new plans and strategies to control, manage, and develop precise sensor chips.…”
Section: Introductionmentioning
confidence: 99%